2014
DOI: 10.1111/jnc.12814
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulatory effects of human mesenchymal stem cells on peripheral blood mononuclear cells in ALS patients

Abstract: In a previous study, we reported that intrathecal injection of mesenchymal stem cells (MSCs) slowed disease progression in G93A mutant superoxide dismutase1 transgenic mice. In this study, we found that intrathecal MSC administration vastly increased the infiltration of peripheral immune cells into the spinal cord of Amyotrophic lateral sclerosis (ALS) mice (G93A mutant superoxide dismutase1 transgenic). Thus, we investigated the immunomodulatory effect of MSCs on peripheral blood mononuclear cells (PBMCs) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 58 publications
1
42
0
Order By: Relevance
“…For example, IDO acts as a pivotal molecule controlling the functional status of Tregs following TLR9 ligation [41]. When MSCs are cocultured with peripheral blood mononuclear cells from patients of amyotrophic lateral sclerosis, IDO levels in the co-cultured MSCs are correlated with the increase in Treg induction [42]. In the present study, we showed that Treg levels were significantly increased in splenocytes after ASCs treatment.…”
Section: Discussionsupporting
confidence: 53%
“…For example, IDO acts as a pivotal molecule controlling the functional status of Tregs following TLR9 ligation [41]. When MSCs are cocultured with peripheral blood mononuclear cells from patients of amyotrophic lateral sclerosis, IDO levels in the co-cultured MSCs are correlated with the increase in Treg induction [42]. In the present study, we showed that Treg levels were significantly increased in splenocytes after ASCs treatment.…”
Section: Discussionsupporting
confidence: 53%
“…Treatment with MSCs was also shown to boost positive adaptive immune responses in ALS, leading to increased infiltration of immune cells into the spinal cord in the animal model [96]. In human beings with ALS or MS, concomitant intrathecal and iv treatment with autologous MSCs led to increased numbers of circulating Treg cells (assessed as CD4+ CD25+ T cells) [97].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 97%
“…Jovicic et al also identified several genes related to rRNA biogenesis (e.g., efg1 and nsr1 ) as significant modifiers of poly(PR) toxicity [17]. Additionally, poly(PR) and poly(GR) peptides colocalize with nucleoli, the site of rRNA synthesis [62]. Although the dysregulation of ribogenesis has been associated with c9orf72 HRE in multiple studies, the mechanism remains poorly understood.…”
Section: Translational Alterations In Different Types Of Als and Als/ftdmentioning
confidence: 99%